Exploring Network Softwarization and Virtualization by Applying SDN/NFV to 5G and IoT - Lin, Bao-Shuh Paul; Lin, Yi-Bing; Tung, Li-Ping; Lin, Fuchun Joseph (Discoveries in Agriculture and Food Sciences, 2018)
The development trends of networking and wireless communications technologies have evolved toward Open Networking (ON), Software Defined Networks (SDN), Network Function Virtualization (NFV), and Disaggregation. ON and SDN/NFV are playing the key roles for softwarization and virtualization (S&V) of next generation networks such as 5th Generation Communications and Networks (5G) and Internet of Things (IoT). This article explores the S&V of 5G & IoT and addresses the challenging issues related to applying SDN/NFV to 5G and IoT. These issues include system performance, end-to-end interoperability, software compatibility, global deployment, integration of SDN and NFV , and shortage of talents. In addition, we describe the research and development status of adapting ON architecture and applying SDN/NFV to 5G and IoT in Taiwan. Finally we report the collaboration between National Chiao Tung University (NCTU) and networking industry in the areas of programmable switches built on top of silicon with Programming Protocol-independent Packet Processor (P4) high-level script language and prototyping an OpenAirIntrface (OAI)-based M-CORD.